Estudo da métrica de Gödel e soluções tipo-Gödel nas gravitações f (R) e f (R,T) - Ferst Júnior, Celso José (2015)
In this work we studied the causality issue on the Gödel and type-Gödel metrics. Then, we examined the problem of violation of causality on the modified gravities f(R) and f(R, T), where R is the curvature scalar and T is the trace of energy-momentum tensor Tµν. The problem of causality is investigated in three situations: (i) it is considered a perfect fluid as content of matter of universe; (ii) the content of matter is the perfect fluid plus a scalar field; and (iii) we have only scalar field as source of matter.